2021
DOI: 10.3390/magnetochemistry7040051
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-Erythrocyte Membrane Vesicles’ Superior T2 MRI Contrast Agents to Magneto-Liposomes

Abstract: Despite their high potential, most of the clinically approved iron oxide (IO)-based contrast agents for magnetic resonance imaging (MRI) have been withdrawn from the market either due to safety issues or lack of sales. To address this challenge, erythrocyte membranes have been used to prepare IO-based T2 contrast agents with superior MRI properties and higher safety margin. A simple formulation procedure has been proposed, and the nanostructures’ morphology and physicochemical properties have been evaluated. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…However, for nanoparticles encapsulated in the aqueous core or conjugated to the surface of liposomes, oleate-coating has been the method most frequently used. In this case, it is expected that hydrophobic nanoparticles have a higher affinity to the phospholipid bilayer [62,63]. Martinez-Gonzales et al reported the synthesis of hydrophobic magnetic nanoparticles which were loaded into the lipid bilayer of the liposome.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%
“…However, for nanoparticles encapsulated in the aqueous core or conjugated to the surface of liposomes, oleate-coating has been the method most frequently used. In this case, it is expected that hydrophobic nanoparticles have a higher affinity to the phospholipid bilayer [62,63]. Martinez-Gonzales et al reported the synthesis of hydrophobic magnetic nanoparticles which were loaded into the lipid bilayer of the liposome.…”
Section: Magnetic Nanoparticlesmentioning
confidence: 99%